(untitled) (Bangladesh Journal of Child Health, 2013)
Background: Acute bacterial meningitis (ABM) is one of the common causes of morbidity and mortality in children. Easy and early diagnostic tool is required for rapid detection of acute bacterial meningitis to reduce mortality and morbidity. Objectives: The study was conducted with the aim to identify the importance of cerebrospinal fluid C- reactive protein (CSF-CRP) to establish the diagnosis of ABM, and to measure the specificity, sensitivity, positive and negative predictive values of CSF-CRP in the diagnosis of Acute Bacterial Meningitis. Methods: This prospective study was carried out in Dhaka Shishu (Children) Hospital during the period of December 2004 to April 2005. Children admitted between age 0- 12 years with fever and convulsion were screened. Patients were divided into three groups on the basis of CSF findings- bacterial meningitis, aseptic meningitis and no meningitis control group. Only CSF culture proven cases were selected as ABM. CSF CRP was measured in all cases along with CSF cytology, biochemistry and culture-sensitivity. Complete were blood count, random blood sugar and other tests also done to treat all cases. All patients were treated adequately (if culture positive according to sensitivity) and were monitored as long as they stayed in hospital. Outcome was assessed clinically during discharge. Results: Twenty patients had acute bacterial meningitis, 15 aseptic meningitis, and 15 cases CSF findings normal and taken as control. CSF-CRP was positive (>6mg/ L) in 35% of the cases of ABM but it was found negative in all aseptic meningitis and in the control groups. Sensitivity of CSF -CRP was low (35%) but specificity was high (100%). The positive predictive value of CSF-CRP was 100% and negative predictive value 53.6%. Among the organisms isolated from acute bacterial meningitis, H. influenzae was the leading pathogen (40%) in infancy followed by S. pneumoniae (35%) and N. meningitidis (5%). Out come of the treatment of CSF-CRP positive ABM cases was found poor (p= 0.035). Conclusion: It is concluded from the study that significant(>6mg/L) level of CRP in CSF is highly specific for diagnosis of ABM and ruled out aseptic meningitis. But negative CSF-CRP could neither exclude pyogenic meningitis nor did it rule out aseptic meningitis. DOI: http://dx.doi.org/10.3329/bjch.v36i3.14275 BANGLADESH J CHILD HEALTH 2012; VOL 36 (3) : 126-132